2018
DOI: 10.1002/jcb.27314
|View full text |Cite
|
Sign up to set email alerts
|

Hsa‐miR‐5582‐3P regulatory effect on TGFβ signaling through targeting of TGFβ‐R1, TGFβ‐R2, SMAD3, and SMAD4 transcripts

Abstract: Transforming growth factor β (TGFβ) signaling pathway which is regulated by factors such as microRNAs (miRNAs) has pivotal roles in various cellular processes. Here, we intended to verify bioinformatics predicted regulatory effect of hsa-miR-5582-3P against TGFβ/SMAD signaling pathway components. Quantitative reverse-transcription polymerase chain reaction (RT-qPCR) analysis indicated a negative correlation of expression between hsa-miR-5582-3P against TGFβ-R1, TGFβ-R2, SMAD3, and SMAD4 putative target genes i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 40 publications
(95 reference statements)
0
3
0
Order By: Relevance
“…Differential expression in disease states has been identified for miR-3182 [38, 39]. It has been reported that overexpression of miR-5582-3P affects TGFβ signaling through targeting [40] and that mirR-6863 is deregulated in FTO knockdown cells [41]. Assessment of the regulatory effects of miRNAs on targets relies on correct identification of miRNA-target interactions.…”
Section: Discussionmentioning
confidence: 99%
“…Differential expression in disease states has been identified for miR-3182 [38, 39]. It has been reported that overexpression of miR-5582-3P affects TGFβ signaling through targeting [40] and that mirR-6863 is deregulated in FTO knockdown cells [41]. Assessment of the regulatory effects of miRNAs on targets relies on correct identification of miRNA-target interactions.…”
Section: Discussionmentioning
confidence: 99%
“… hsa-miR-874 Decreased expression was associated with poor overall survival of ESCC patients, targets STAT3 [ 101 ]. hsa-miR-5585 Regulates cell cycle progression in human colorectal carcinoma cells, decreases expression of TGFβ-R1 , TGFβ-R2 , SMAD3 , and SMAD4 [ 102 ]. AAA—aortic abdominal aneurysm, AMI—acute myocardial infraction, CAD—coronary artery disease, EGFR—endothelial growth factor receptor, ESCC—esophagal squamous cells carcinoma, HCC—human colorectal cancer, HEY1—hairy/enhancer-of-split related with YRPW motif protein 1, HIF-1α—hypoxia induced factor 1α, HOXB1—homeobox B1, hUCMSCs—human umbilical cord mesenchymal stem cells, MALAT1—metastasis associated lung adenocarcinoma transcript 1, MAPK—mitogen activated protein kinase, mTOR—mammalian target of rapamycin, NF-κB—necrotic factor κB, NOTCH—translocation-associated protein, PI3K/AKT—phosphoinositide 3-kinases/protein kinase B, PTEN—phosphatase and tensin homolog deleted on chromosome ten, T2D—type 2 diabetes, TAA—thoracic aortic aneurysm, TGF-β—tumor growth factor β, TGFβ-R1—tumor growth factor β receptor 1, TGFβ-R2—tumor growth factor β receptor 2, SIRT7—sirtuin 7, SMAD3—decapentaplegic homolog 3, SMAD4—decapentaplegic homolog 4, STAT3—signal transducer and activator of transcription 3, SUFU—suppressor of fused homolog, Wnt—wingless-type MMTV integration site family of genes, VEGF—vascular endothelial growth factor, VEGFA—vascular endothelial growth factor A, VEGFR2—vascular endothelial growth factor receptor 2, VSMCs—vascular smooth muscle cells.…”
Section: Abdominal Aorta Aneurysm and Control Groups Constructionmentioning
confidence: 99%
“…Thus, elaborating the molecular regulators of this pathway helps in understanding the mechanisms that leads to diseases. TGFβ signaling pathway has been reported to be regulated by several known miRNAs [23][24][25][26].…”
Section: Discussionmentioning
confidence: 99%